Petroleum hydrocarbon contamination of groundwater in Suez: causes severe fire risk - Afifi, Sameh M., author; Colorado State University, publisher (Colorado State University. Libraries, 2004)
One of the major contributing causes to the fire that killed 8 persons in August 2000 and the Suez Petroleum region was the petroleum hydrocarbon releases to the subsurface groundwater at the SUEZ Geographical Region. The Suez petroleum geographic region is shared by several oil companies. Several of these companies have been in operation of oil refining, processing and petroleum products distribution activities for more than seventy years. The combined effects of petroleum related activities and war strikes have resulted in tremendous impacts on the safety and environmental conditions at the region. Hydrocarbon leaks and spills have resulted in serious contamination to shallow groundwater and became the major fire safety hazard in addition to posing serious environmental risk. Due to financial reasons and urge of immediate correction action, the conducted investigation focused on fire potential in order to minimize the risk. To properly characterize and evaluate the impacted soils, an intensive site characterization was performed. Sixty-three (63) soil borings were drilled in different locations around the region. Soil samples were collected from different depths and then analyzed for total petroleum hydrocarbon (TPH) to determine its content in the soil. In order to assess the quantities and locations of free hydrocarbon product floating on top of the groundwater surface, fifty-three (53) soil boring were converted to monitoring wells. Based on the detected levels of free product inside the installed monitoring wells network, the groundwater hydrocarbon plume varies in thickness from 6" to over 40". Free product samples were collected from selected monitoring wells. The samples were sent to SPL Labs in Houston to perform PIANO analysis (Paraffins, Isoparaffins, Aromatics, Napthenes, and Olefins) and give a complete breakdown of all the chemical components which comprise the hydrocarbons. Chemical analysis of the free product collected from the subsurface that several sources of petroleum hydrocarbon releases are responsible for the free product plume. Mazot, solar (diesel) and gasoline (benzene) range petroleum hydrocarbons all exist in the subsurface. Three different groundwater plumes have been identified. Existing conditions at the site guarantee that upon an ignition source is present, the soils and free product on top of groundwater can and will maintain the fire to the furthest extent. Such conditions will be extremely dangerous and difficult for fire fighting teams. This paper presents the taken steps for investigation petroleum hydrocarbon contamination to minimize the fire risks. The present procedures will assist scientists and professionals in the field when investigating similar conditions.
Hydrology days 2004
AGU hydrology days 2004
24th annual AGU hydrology days was held at Colorado State University on March 10-12, 2004.